Histone methyltransferase MLL4 protects against pressure overload-induced heart failure via a THBS4-mediated protection in ER stress - Xiang-Min Meng; Qiu-Yu Pang; Zhen-Fang Zhou; Jing-Han Yuan; Lu You; Qi-Pu Feng; Bing-Mei Zhu (Elsevier, 2024)
Pressure overload-induced pathological cardiac hypertrophy eventually leads to heart failure (HF). Unfortunately, lack of effective targeted therapies for HF remains a challenge in clinical management. Mixed-lineage leukemia 4 (MLL4) is a member of the SET family of histone methyltransferase enzymes, which possesses histone H3 lysine 4 (H3K4)-specific methyltransferase activity. However, whether and how MLL4 regulates cardiac function is not reported in adult HF. Here we report that MLL4 is required for endoplasmic reticulum (ER) stress homeostasis of cardiomyocytes and protective against pressure overload-induced cardiac hypertrophy and HF. We observed that MLL4 is increased in the heart tissue of HF mouse model and HF patients. The cardiomyocyte-specific deletion of Mll4 (Mll4-cKO) in mice leads to aggravated ER stress and cardiac dysfunction following pressure overloading. MLL4 knockdown neonatal rat cardiomyocytes (NRCMs) also display accelerated decompensated ER stress and hypertrophy induced by phenylephrine (PE). The combined analysis of Cleavage Under Targets and Tagmentation sequencing (CUT&Tag-seq) and RNA sequencing (RNA-seq) data reveals that, silencing of Mll4 alters the chromatin landscape for H3K4me1 modification and gene expression patterns in NRCMs. Interestingly, the deficiency of MLL4 results in a marked reduction of H3K4me1 and H3K27ac occupations on Thrombospondin-4 (Thbs4) gene loci, as well as Thbs4 gene expression. Mechanistically, MLL4 acts as a transcriptional activator of Thbs4 through mono-methylation of H3K4 and further regulates THBS4-dependent ER stress response, ultimately plays a role in HF. Our study indicates that pharmacologically targeting MLL4 and ER stress might be a valid therapeutic approach to protect against cardiac hypertrophy and HF.